1996
DOI: 10.1111/j.1600-0587.1996.tb00233.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect and extent of heavy grazing by reindeer in oligotrophic pine heaths in northeastern Fennoscandia

Abstract: Thirty and fifty years old exclosures established in northeastern Fennoscandia in lichen‐rich oligotrophic pine Pinus sylvestris forests on podzolised soil were used to study the effect of reindeer grazing on pine fine roots, microbial activity, and on bryophyte, dwarf shrub and lichen biomasses. There were significantly less lichens, especially Cladina stellaris, at grazed than at ungrazed sites. Coverage of other lichens like C. arbuscula and C. rangiferina and bryophytes, especially Dicranum spp., benefitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
94
4
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 21 publications
7
94
4
4
Order By: Relevance
“…As a consequence of increased tall herb abundance, dwarf shrubs were found to be the losers in the subalpine exclosure. These findings contrast with results reported from arctic environments, where reindeer grazing mainly reduced the abundance of dwarf shrubs (Väre et al 1996). The contrasting results can be attributed to the differences in grazers, plant communities and climate.…”
Section: Discussioncontrasting
confidence: 56%
“…As a consequence of increased tall herb abundance, dwarf shrubs were found to be the losers in the subalpine exclosure. These findings contrast with results reported from arctic environments, where reindeer grazing mainly reduced the abundance of dwarf shrubs (Väre et al 1996). The contrasting results can be attributed to the differences in grazers, plant communities and climate.…”
Section: Discussioncontrasting
confidence: 56%
“…The differences between individual studies may be due to different experiment and study designs and spatial scales. As far as we know, our estimate of the difference between the lichen biomass in the ungrazed and grazed sites is the largest observed among different studies to date (Väre et al 1996;Susiluoto et al 2008;Olofsson et al 2010;Köster et al 2013). The second highest difference was observed by Väre et al (1996) who reported that the lichen biomass in the ungrazed sites was nine-fold compared with the estimate in the grazed sites.…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, grazing and trampling by reindeer generally leads to a decline in lichen abundance (Helle and Aspi 1983;Ja¨gerbrand and Alatalo 2015), and could partly explain the significant decrease in lichen diversity at Dovrefjell. Bryophytes, however, tend to benefit from grazing (Va¨re et al 1996;Austrheim and Eriksson 2001;Takala et al 2014). For instance, Helle and Aspi (1983) observed an increase in small-bodied mosses (e.g.…”
Section: Other Possible Drivers Of Changes In Vegetationmentioning
confidence: 99%